2022
DOI: 10.22159/ijap.2022v14i1.43328
|View full text |Cite
|
Sign up to set email alerts
|

Bioanalytical Rp-HPLC Method Development and Validation of Clopidogrel Bisulfate in Wistar Rat Plasma and Its Application to Pharmacokinetic Study

Abstract: Objective: A novel, simple, precise, accurate, sensitive, and reproducible HPLC method for determining clopidogrel bisulfate in Wistar rat plasma was developed and validated. Methods: The chromatographic separation was performed using Xterra C18 (250 x 4.6 mm, 5μ) column. Mobile phase composed of Acetonitrile ACN: 0.05M potassium dihydrogen orthophosphate buffer pH 4.2 and in the ratio of 75:25% v/v at a flow rate of 1.2 ml/min. Detection was carried out using a PDA detector at 220 nm. The bioanalytical clopid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…The robustness appertaining developed method for tulobuterol hydrochloride was deliberated by discretely varying the flow rate (±0.2 ml/min) of the mobile phase as mentioned in the methodology; further retention times were evaluated. The %RSD was within 2%, which revealed robustness and reliability of the developed method [21].…”
Section: Robustnessmentioning
confidence: 60%
See 1 more Smart Citation
“…The robustness appertaining developed method for tulobuterol hydrochloride was deliberated by discretely varying the flow rate (±0.2 ml/min) of the mobile phase as mentioned in the methodology; further retention times were evaluated. The %RSD was within 2%, which revealed robustness and reliability of the developed method [21].…”
Section: Robustnessmentioning
confidence: 60%
“…The peak areas of spiked plasma and blank samples were compared. If there exists any interference with the retention time of tulobuterol hydrochloride, the peak area of the blank should be within 20 % peak area of the tulobuterol peak [20,21].…”
Section: Specificitymentioning
confidence: 99%
“…The LOQ value were 7.53 µg/ml for EGCG and 3.05 µg/ml for curcumin. These low values demonstrated that the developed method was very sensitive to quantifying EGCG and curcumin [39].…”
Section: Sensitivitymentioning
confidence: 99%
“…Through the calculation of within and between batch fluctuations at 4 QC sample levels (5.00, 25.00, 50.00, and 75.00 ng/ml) in 6 repetitions, the accuracy and precision of this approach were maintained under control [20,21]. Table 2 shows maralixibat's findings for accuracy and precision.…”
Section: Precision and Accuracymentioning
confidence: 99%